Leadership Development Experiences of Women Leaders in State-Owned Enterprises in Indonesia - Dewi, Yuliana; Rachmawati, Riani (The South East Asian Journal of Management, 2014)
Similar to many other countries in the world, Indonesia has been experiencing the increasing number of women workers participation both in formal and informal sectors. While in formal sector the number of female employees has increased from around 10 millions in 2008 to nearly 13 millions in 2011; in informal sector the figure is even doubled: more than 28 millions in 2008 to more than 30 millions in 2011. However to date, women workers are associated with low-skilled, low-wage workers who work in precarious working environment. Women are seldom hold managerial position both in public and private sector. The proportion of women in Indonesia who sit in the board of directors is only 6% from the entire women workers. Thus, this research aims to explore their development experience along the way. In order to obtain initial information, interviews with nine women managers from State-Owned Enterprises (SOEs) were conducted. SOEs were chosen for convenience reason. The research indicates the low ratio number of women in SOEs management team although there is an optimism that the number would increase. Key point discovered in this research is that development experience is mainly done by the participants own initiatives whereas organisational supports are found very limited. This findings will be further explored and confirmed by involving more women managers from various sectors.